Sisters or strangers? : immigrant, ethnic and racialized women in Canadian history - Iacovetta, Franca, 1957-; Epp, Marlene, 1958- (Studies in gender and history, 2016)
"Spanning more than two hundred years of history, from the eighteenth century to the twenty-first, Sisters or Strangers? explores the complex lives of immigrant, ethnic, and racialized women in Canada. Among the themes examined in this new edition are the intersection of race, crime, and justice, the creation of white settler societies, letters and oral histories, domestic labour, the body, political activism, food studies, gender and ethnic identity, and trauma, violence, and memory."--